Insect Raf kinase inhibition factor - CHEN XUEXIN; WANG ZHIZHI; GU LICHENG (2025)
The invention discloses an insect Raf kinase inhibition factor, which is a protein coded by a CvBV28-5 gene of polydDNA (deoxyribonucleic acid) virus of cotesia vestalis, and the amino acid sequence is shown as SEQ ID No.22 or SEQ ID No.8. The invention further discloses a preparation method of the insect Raf kinase inhibition factor. The nucleotide sequence of the gene for coding the inhibition factor of the insect Raf kinase is as shown in SEQ ID NO. 21 or SEQ ID NO. 7. The invention proves that CvBV28-5 interacts with Raf protein of plutella xylostella for the first time, so that the peak value of 20E titer in hemolymph of larvae of plutella xylostella is influenced, the ecdysis process of the larvae of plutella xylostella is prolonged, and a new gene resource is provided for improving the biological control efficiency of parasitic wasps and developing novel transgenic insect-resistant crops. 本发明公开了一种昆虫Raf激酶的抑制因子，为菜蛾盘绒茧蜂多分DNA病毒的CvBV_28-5基因编码的蛋白，氨基酸序列如SEQ ID No.22或SEQ ID No.8所示。编码所述昆虫Raf激酶的抑制因子的基因，核苷酸序列如SEQ